Rehabilitasi Berbasis Pesantren bagi Penyalah Guna Narkotika sebagai Bentuk Perlindungan Hukum - Vivi Ariyanti; Bani Syarif Maula (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
Illicit trafficking and narcotics abuse cause many victims and social problems. In implementing legal protection policies, the National Narcotics Agency (BNN) of Banyumas Regency undertakes rehabilitation efforts for narcotics abuse by collaborating with the Nurul Hikmah Islamic Boarding School in Cilongok. This study aims to analyze the form of legal protection for narcotics abusers in the Banyumas district, and the rehabilitation process for narcotics abusers based on Islamic boarding schools at Nurul Hikmah Islamic Boarding School, Cilongok Banyumas. This research is a type of empirical normative research. This study found that the BNN provides legal protection for narcotics abuse by placing them in institutions or rehabilitation centers. Based on the theory of victim protection, the steps and actions taken by the Banyumas Regency BNN are correct, namely separating the criminal offender (narcotics trafficker) from the victim (addicts and victims of narcotics abuse). In terms of carrying out rehabilitation, BNN Banyumas Regency has collaborated with the Nurul Hikmah Islamic Boarding School in Cilongok. The rehabilitation process at Nurul Hikmah Islamic Boarding School in Cilongok is an indicator that the government has carried out its obligations (in accordance with the UU No. 35/2009 about: Narcotics) in carrying out legal protection for victims of narcotics abuse in the form of pesantren-based social rehabilitation so that they can return to live a good life according to religious rules and principles.